Earth crust deep structure and dynamics study at the Vernadsky station by geoelectromagnetic methods – present state and perspectives - Korepanov, V.; Milinevsky, G.; Maksymchuk, V.; Ladanivsky, B.; Nakalov, Ye. (Ukrainian Antarctic Journal, 2004)
The Earth crust deep structure at the Academic Vernadsky station was studied by two methods: magnetotelluric sounding (MTS) and tectonomagnetic profiling (TMP). New electromagnetic instrumentation of the station is shortly described and its main technical parameters are given. The measurements results obtained by both experimental methods are presented and first interpretation attempts are made and discussed. The TMP results showed good coincidence of static (∆Т) and dynamic (∆∆Т) magnetic field anomalies plots along the selected profile and reveal intense dynamic magnetic anomaly caused by modern geodynamic processes. Their interpretation allows identifying the tectonic through of submeridional direction in the station region with intensive geodynamic processes: mean speed of the sublatitude local strain there can be estimated within 6 Bar/year. The MTS data processing showed clearly seen orientation of main directions azimuths of impedance tensor: 50° for maximal impedance and 140° for minimal one, by this maximal impedance azimuth coincides with the continental shore line direction in the region. Their interpretation indicates high probability of the existence of deep trough (or a set of troughs) along the western shore of the Antarctic Peninsula and of the complicated 3D geoelectric structure there.